Understanding motivation of a recreational cyclists - Mohamad Nizam Nazarudin; Zakiah Noordin; Mohd Firdaus Abdullah (International Research Journal of Education and Sciences (IRJES), 2020)
Cycling has been shown to have positive benefits on social interaction, mood and self-esteem, and levels of depression and stress. The purpose of this study was to measure competitive cyclist’s motivation. Fifty-nine cyclists (29 males and 30 females) who were registered participant in UMS Fun Ride completed a Cyclists’ Motivation Instrument (Brown, O’Connor & Barkatsas, 2009). Participants ranged in age from 19 to 32 years (21.73± 2.30). Descriptive and Inferential statistics (t-test and one-way ANOVA) were employed to analyse the data. Social, embodiment, self presentation, exploring environments, and physical health outcomes are at the high level. An embodiment is the highest meanwhile self-presentation is the lowest motivation motive. No significant differences were observed between genders, ages, cycling speed and BMI for any of the Cyclists’ Motivation component. Understanding cultural, subcultural and ecological factors of participation in cycling are by a deeper understanding of participant’s practices. It is recommended that further psychometric analyses should be conducted with other groups of cyclists such as club recreational members to harmonize the competing needs of subgroups and focus policy and support for this life affirming pursuit.